2000
DOI: 10.1034/j.1600-0781.2000.160505.x
|View full text |Cite
|
Sign up to set email alerts
|

Extended extracorporeal photochemotherapy with extracorporeal administration of 8‐methoxypsoralen in systemic sclerosis. An Austrian single‐center study

Abstract: Extended EXP with extracorporeal administration of 8-MOP is a safe and well tolerated treatment modality. However, it provides only (minor) improvement of skin changes of a subset of SSC patients and does not beneficially influence extracutaneous manifestations and quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 25 publications
0
20
0
2
Order By: Relevance
“…In somewhat larger numbers of patients, improvements in the skin manifestations of systemic sclerosis have been demonstrated, but no changes in, or progression of, visceral involvement during treatment was observed. 19,20 In contrast, long-term follow-up of 5 patients treated with ECP on 2 successive days per month for a mean of 59 (range 54-89) months indicated that, in selected patients with early disease, ECP produced improvements or stabilization in a range of symptoms, including skin thickening, joint mobility, pulmonary function studies, oral aperture, and functional index. 21,22 There have been 3 randomized, controlled studies of ECP in systemic sclerosis.…”
Section: Ecp May Improve Skin Involvement In Systemic Sclerosismentioning
confidence: 71%
“…In somewhat larger numbers of patients, improvements in the skin manifestations of systemic sclerosis have been demonstrated, but no changes in, or progression of, visceral involvement during treatment was observed. 19,20 In contrast, long-term follow-up of 5 patients treated with ECP on 2 successive days per month for a mean of 59 (range 54-89) months indicated that, in selected patients with early disease, ECP produced improvements or stabilization in a range of symptoms, including skin thickening, joint mobility, pulmonary function studies, oral aperture, and functional index. 21,22 There have been 3 randomized, controlled studies of ECP in systemic sclerosis.…”
Section: Ecp May Improve Skin Involvement In Systemic Sclerosismentioning
confidence: 71%
“…34 However, the influence of ECP on the progression of visceral organ involvement could not be consistently demonstrated in these uncontrolled trials. 35,36 The first randomised, observer blinded, prospective trial of ECP in SSc compared ECP with D-penicillamine, a substance with purported antifibrotic activity, in 79 patients of recent disease onset. 37 A skin score was used as the primary endpoint and 21 of 31 patients (68%) showed an improvement after 6 months of ECP compared with eight of 25 patients (32%) given D-penicillamine.…”
Section: Systemic Sclerosismentioning
confidence: 99%
“…In that trial, ECP was given on two consecutive days monthly for 12 months. In the study of Enomoto et al and the trial of Muellegger and colleagues, ECP sessions were performed every 4 weeks on two consecutive days [5,6]. They reported a minor improvement of skin changes only.…”
Section: Discussionmentioning
confidence: 95%
“…Formerly, clinical trials demonstrated the efficacy of ECP in SSc; however, they investigated clinical parameters only, such as skin or joint manifestations [3][4][5][6]. Our workgroup was the first to investigate the immunomodulatory effects of ECP in SSc patients [7].…”
Section: Introductionmentioning
confidence: 98%